Facile synthesis of a WOx/CsyWO3 heterostructured composite as a visible light photocatalyst. Issue 13 (12th February 2018) - Tahmasebi, N.; Madmoli, S.
Abstract : In this work, a WO x /Cs y WO3 heterostructured composite photocatalyst was synthesized via a simple pyrolysis method followed by heat treatment under a reducing atmosphere. Abstract : In this work, a WO x /Cs y WO3 heterostructured composite was synthesized via a simple pyrolysis method followed by heat treatment under a reducing atmosphere. Optical absorption results revealed the WO x /Cs y WO3 heterostructured composite exhibits a strong absorption tail in the Vis and NIR regions which could have important implications for its photoactivity. The photocatalytic performance of synthesized samples with different Cs/W molar ratios was evaluated by the photodegradation of RhB in aqueous solution under simulated solar light irradiation. The results revealed that the photocatalytic activity of the WO x /Cs y WO3 composite is much higher than those of pure tungsten bronze (Cs x WO3, x = 0.32, and 0.5) and pure WO2.83 samples, where 90% RhB was degraded after 160 min irradiation. Also, the WO x /Cs y WO3 composite exhibits excellent photocatalytic activity for the degradation of MO, MB, RhB, and MG aqueous solution under visible light irradiation. It is proposed that the higher photocatalytic activity of the WO x /Cs y WO3 composite could be attributed to the greater surface adsorption of dye molecules, intense light absorption in the visible and NIR regions, and photogenerated electron–hole separation.